2022
DOI: 10.7203/realia.29.23810
|View full text |Cite
|
Sign up to set email alerts
|

El portafolio digital como herramienta de aprendizaje en la supervisión de prácticas durante la COVID-19

Abstract: Professional practice is fundamental because it represents the link between theoretical training and the application of skills and knowledge in the professional field. In March 2020, howe- ver, COVID-19 obliged teaching staff to redesign their professional practicums to ensure that they satisfied the requirements established for their training activities. In this context, digital portfolios were seen as a fundamental tool. The main aim of this article is to analyse the usefulness of the digital portfolio as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The collaborative process of e-portfolios implementation contains four main types: teacher-student (Abuzaid et al, 2021;Miyoshi et al, 2021;Modise, 2021;Mudau & Modise, 2022;Rodriguez et al, 2022;Viscarret et al, 2022;), student-student (Abuzaid et al, 2021;Ismailov & Laurier, 2022;Modise, 2021;Mudau & Modise, 2022;Rodriguez et al, 2022;Viscarret et al, 2022), with other professionals (Miyoshi et al, 2021), and whole community collaboration (Abuzaid et al, 2021;Ismailov & Laurier, 2022;Modise, 2021;Mudau & Modise, 2022). We argue that learning community collaboration, comprised of the two main protocols of CoI and virtual teams, encompasses all other kinds of collaboration.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The collaborative process of e-portfolios implementation contains four main types: teacher-student (Abuzaid et al, 2021;Miyoshi et al, 2021;Modise, 2021;Mudau & Modise, 2022;Rodriguez et al, 2022;Viscarret et al, 2022;), student-student (Abuzaid et al, 2021;Ismailov & Laurier, 2022;Modise, 2021;Mudau & Modise, 2022;Rodriguez et al, 2022;Viscarret et al, 2022), with other professionals (Miyoshi et al, 2021), and whole community collaboration (Abuzaid et al, 2021;Ismailov & Laurier, 2022;Modise, 2021;Mudau & Modise, 2022). We argue that learning community collaboration, comprised of the two main protocols of CoI and virtual teams, encompasses all other kinds of collaboration.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have identified multiple non-negligible concerns in educational e-portfolio implementation: technical difficulties, learners' unfamiliarity, a lack of common knowledge of how to use e-portfolios effectively, etc. (Abuzaid et al, 2021;Modise, 2021;Mudau & Modise, 2022;Viscarret et al, 2022;Zhang & Tur, 2022). These concerns stem from insufficient guidance and support from teachers and learning peers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations